Evaluation of a mining project using Discounted Cash Flow analysis, Decision Tree analysis, Monte Carlo Simulation and Real Options using an example - Topal, Erkan (Inderscience Publishers, 2008)
Investments in the mining and minerals industry are considered to be risky. The major challenge of project evaluation is how to deal with the uncertainty involved in capital investment. Discounted Cash Flow (DCF) methods, Decision Trees (DT), Monte Carlo Simulation (MCS) and Real Options (RO) are commonly used for evaluating mining projects. This paper briefly reviews the previous studies, outlines and summarises above four methods. Subsequently it employs these methods to evaluate a mining project where the decision whether or not to open the mine is considered. Pros and cons of investigated methods are discussed in the final section. © 2008 Inderscience Enterprises Ltd.